Güteraustausch und regionale Mobilität im Kallawaya-Tal (Bolivien) - Schoop, Wolfgang (ERDKUNDE, 1982)
The peripheral and isolated location of the Charazani Valley requires an intensive commercial exchange within the region. The vertical control, the system of markets and the caravan traffic are analyzed in respect of their significance for commercial exchange. Linkage areas within the valley system can be differentiated on the basis of the frequency of short journeys and of the main caravan routes. Thanks to the manifold contacts with Charazani, an immediat catchment area can be defined. Outside relations are traditionally brought about by medicine traders, but marked contacts outside the province also play a role. Beside the journeys of the medicine traders there is a seasonal migration of workers, which is often a first step towards final emigration.